2021
DOI: 10.1108/edi-02-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous practices and conflicting interests: why immigrants end up in uncertain employment

Abstract: PurposeThe aim of this study is to investigate why many immigrants end up in uncertain employment.Design/methodology/approachThe paper describes a qualitative case study of three nursing homes in Oslo (Norway), which investigates immigrant employment and recruitment-related practices. Practice theory is used as the theoretical and methodological framework. The study takes an ethnographic approach and combines participant observation, semi-structured shadowing, qualitative interviews and document review.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…When managers refrained from using care assistants as extra-staff for a longer period, immigrants faced difficulties accumulating enough work hours to acquire formal healthcare qualifications. Immigrants then remained unskilled workers in insecure employment conditions (Lindheim 2021a), and consequently, the healthcare sector continues to suffer from a lack of qualified resources. Studies on the integration of immigrants into the labor market have argued for an introductory program that grants immigrants enough time and resources to obtain formal qualifications (Djuve et al 2017), but initiatives are often inhibited by the conflict between different interests (Djuve & Kavli 2019).…”
Section: Effects Of Managers' Inclusion-related Practices On Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…When managers refrained from using care assistants as extra-staff for a longer period, immigrants faced difficulties accumulating enough work hours to acquire formal healthcare qualifications. Immigrants then remained unskilled workers in insecure employment conditions (Lindheim 2021a), and consequently, the healthcare sector continues to suffer from a lack of qualified resources. Studies on the integration of immigrants into the labor market have argued for an introductory program that grants immigrants enough time and resources to obtain formal qualifications (Djuve et al 2017), but initiatives are often inhibited by the conflict between different interests (Djuve & Kavli 2019).…”
Section: Effects Of Managers' Inclusion-related Practices On Immigrantsmentioning
confidence: 99%
“…Previous research has underscored the central role of managers in immigrants' experiences of inclusion at work (Kirton & Greene 2021;Sandal et al 2013). Other researchers studying organizational and managerial practices (Janssens & Steyaert 2019;Lindheim 2021a;Ortlieb & Sieben 2014) have found that these practices are ambiguous and may enhance as well as hinder the inclusion of immigrants. Despite these previous studies, we have a limited understanding of how a regulated work context shapes managers' practices.…”
mentioning
confidence: 99%
“…After a preliminary analysis of the data material from observation and interviews, validation meetings were held with a selected group of managers in two of the nursing homes. 1 A central finding of the study concerned the employment situation of immigrant employees without formal healthcare credentials (Lindheim, 2021). Tables that displayed the numbers and percentages of employees in different categories of healthcare positions and the size of their employment contracts were presented in the validation meetings.…”
Section: Validation Of Preliminary Analysis In Focus Groupsmentioning
confidence: 99%
“…When the informants examined the statistics on employee categories and employment contracts, they offered new information of how the system regulated these issues in the nursing homes, and they argued for their positions and priorities with reference to the other nursing homes. The tendency for employees without formal healthcare credentials in the nursing homes to remain in precarious employment (Lindheim, 2021) was an issue that stood out more clearly after the analysis of the data material. The validation meetings thus offered an opportunity to probe further into this issue, which had not been as evident during observations and interviews.…”
Section: Generating New Datamentioning
confidence: 99%
“…2. Studien er en del av et større ph.d.-prosjekt om kulturelt mangfold og inkludering i arbeidslivet (Lindheim, 2021), og kun deler av det totale datamaterialet benyttes i denne artikkelen. Artikkelens tema er berørt i alle intervjuene og kommer til uttrykk i feltnotater fra observasjonsmaterialet på en slik måte at det ikke er naturlig å gjøre en ytterligere avgrensning av hvilke deler av det totale datamaterialet som benyttes.…”
Section: Metodeunclassified